Classificação cinemática de AGNs: busca por feedback em galáxias do MaNGA - Rosin Gomes, Clara; Martins Souto, Diogo; André Riffel, Rogemar (Cadernos de Astronomia, 2024)
Galaxies with active nuclei (AGN) have a central supermassive black hole (SMBH) that emits outflows and jets of radiationand particles. In some cases, this SMBH interferes with the dynamics of the host galaxy, altering its star formation. Sucha phenomenon is called feedback. In this work, a sample of 62 galaxies present in Sandro B. Rembold et al. (2017) [1]observed by MaNGA to determine which are likely to present a feedback process. To do this, we examine the velocityfields of the stars and the Hα gas of each galaxy to check whether the rotation of both parameters is similar, since galaxiesthat have different velocity fields are likely to be undergoing feedback processes. The classifications used in this workare separated into three classes: regular pattern velocity field (CVPR), irregular pattern velocity field (CVPI) and counter-rotating velocity field (CVCR). Each galaxy in the sample also has its nuclear and extranuclear regions classified intoseyfert, LINER, composite or star-forming region. This is done by analyzing the BPT diagram of each galaxy analyzed.According to the aforementioned classifications, a study can be made of the proportion of each type of classification foreach type of AGN.
Keywords: Astrophysics; black hole; galaxy